WORKFORCE ECOSYSTEM DEVELOPMENT AT HOSPITAL X SURABAYA - Putri, Errytrina Kurnia; Setianto, Budhi; Adriansyah, Agus Aan (Jurnal Manajemen Kesehatan Indonesia, 2024)
X Hospital is one of the hospitals in Surabaya that continues to improve its medical services following several negative reviews found on Google Business between January and April 2024. These reviews suggest that human resource performance, particularly in patient care, needs improvement. In response, the hospital is focusing on internal development by cultivating a workforce ecosystem that includes organic employees, non-organic employees, and interns. This study aims to analyze the development of the workforce ecosystem at Manyar Hospital by evluating employee performance, skill training, and on-the-job training among 116 organic employees, 88 non-organic employees, and 20 interns, with a sample size of 65 participants. Descriptive statistical analysis was employed, with samples selected through convenience sampling. The results indicated that, for employee performance, the highest mean value was found in supervisor social support, while the lowest was found in empowerment. For skill training, the highest mean value was found in the ability to ask, while the lowest was found in self-control. For on-the-job training, the highest mean value was found in the effect on the job, employee training, and deductive and inductive on-the-job training strategies, while the lowest mean was found in structured on-the-job training in developing nations.